Coronavirus Disease 2019 Infection and ABO Blood Groups in a Hemodialysis Cohort in the United Arab Emirates - Ayman Al Madam; Wasim Ahmed; Ali Abdul Kareem Al Obaidli; Edward R Smith; Stephen G Holt (Saudi Journal of Kidney Diseases and Transplantation, 2022)
Some epidemiological data have implicated blood groups in susceptibility to coronavirus disease 2019 (COVID-19) infection. We were interested to see if there was any apparent effect of different ABO blood groups on susceptibility to COVID-19 infection in unvaccinated hemodialysis (HD) patients, as they had a high rate of mortality from this infection. Blood group O has been suggested to be protective against COVID-19 infection; however, since the ABO frequency is affected by ethnicity, we looked at infection frequency and blood group and corrected the expected frequency for the ethnicity of our cohort. We examined 249 HD patients presenting with a positive COVID-19 polymerase chain reaction regarding their ABO blood group and compared the ABO frequencies with published data for the United Arab Emirates (UAE), as well as international and historical ABO data on dialysis frequency. Although there was an apparent protective effect of blood group O when we compared blood group frequencies with the UAE data, this disappeared when corrected for ethnicity. We concluded that any association of the ABO blood group with COVID-19 infection is unlikely to be of major importance and should not be used to reassure patients that they are mildly protected against COVID-19 without vaccination.